Rapid Fabrication of Cell-Laden Alginate Hydrogel 3D Structures by Micro Dip-Coating - Ghanizadeh Tabriz, Atabak; Mills, Christopher G.; Mullins, John J.; Davies, Jamie A.; Shu, Wenmiao (Frontiers in Bioengineering and Biotechnology, 2017)
Development of a simple, straight-forward 3D fabrication method to culture cells in 3D, without relying on any complex fabrication methods, remains a challenge. In this paper, we describe a new technique that allows fabrication of scalable 3D cell-laden hydrogel structures easily, without complex machinery: the technique can be done using only apparatus already available in a typical cell biology laboratory. The fabrication method involves micro dip-coating of cell-laden hydrogels covering the surface of a metal bar, into the cross-linking reagent CaCl2 or BaCl2, to form hollow tubular structures. This method can be used to form single- or multi-layered tubular structures. This fabrication method uses alginate hydrogel as the primary biomaterial and secondary biomaterial could be added deepening on the desired application. We demonstrate the feasibility of the method, and the survival and normal responsiveness of cells within these tubular structures using mouse dermal embryonic fibroblast cells and human embryonic kidney 293 cells containing a tetracycline responsive red fluorescence protein (tHEK cells).